BESARAN PENGARUH POLA ASUH OTORITER TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI - Zahwa Azzahra, Andhieni; Kurnia Jayadinata, Asep; Nikawanti, Gia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Social and emotional development is an important aspect of early childhood growth and development, influenced by various factors, including parenting styles. One parenting style that has received much attention is authoritarian parenting, a parenting style that emphasizes obedience, strict control, and one-way communication. This study used a quantitative method with a simple linear regression approach to analyze the influence of authoritarian parenting on the social and emotional aspects of early childhood. The study respondents consisted of parents or guardians of children aged 4–6 years and were selected using a purposive sampling technique. Data collection was carried out through a questionnaire distributed online using Google Forms. The analysis results showed a correlation coefficient (R) of 0.067, indicating a very low relationship between authoritarian parenting and the social and emotional aspects of early childhood. The coefficient of determination (R²) of 0.005 indicates that authoritarian parenting only contributes 0.5% to children's social and emotional development, while 99.5% is influenced by other factors outside the study. These results indicate that authoritarian parenting does not significantly influence the social and emotional development of early childhood. This finding indicates that children's social and emotional development is complex and influenced by various factors, such as the family environment, school, peers, and the social experiences children experience in their daily lives.